2014
DOI: 10.1111/jac.12079
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Carbon Isotope Discrimination as an Accurate Indicator of Water‐Use Efficiency in Sunflower Genotypes Subjected to Five Stable Soil Water Contents

Abstract: Background: This article evaluates the potential of intraspecific variation for whole-root hydraulic properties in sunflower. We investigated genotypic differences related to root water transport in four genotypes selected because of their differing water use efficiency (JAC doi: 10.1111/jac.12079. 2014). We used a pressure-flux approach to characterize hydraulic conductance (L 0) which reflects the overall water uptake capacity of the roots and hydraulic conductivity (Lp r) which represents the root intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Lambrides et al ( 2004 ) and Adiredjo et al ( 2014a ) showed significant correlations between whole-plant TE and CID in sunflower, while a lack of relationship between CID and TE has been reported previously in other species (Hammer et al, 1997 ; Turner et al, 2007 ; Devi et al, 2011 ). In our study, the lack of correlation could be a consequence of the low variability present in the genotypes analyzed (1.0%0 range), as compared to those of previous studies: 4.4%0 (Lambrides et al, 2004 ), 3.4%0 (Adiredjo et al, 2014a ), 2.5%0 (Virgona et al, 1990 ; Virgona and Farquhar, 1996 ). Unlike other studies in which the analyzed genotypes were selected for showing a wide range of CID, the low variability for this trait in our study may have allowed the detection of significant associations between TE and other traits.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lambrides et al ( 2004 ) and Adiredjo et al ( 2014a ) showed significant correlations between whole-plant TE and CID in sunflower, while a lack of relationship between CID and TE has been reported previously in other species (Hammer et al, 1997 ; Turner et al, 2007 ; Devi et al, 2011 ). In our study, the lack of correlation could be a consequence of the low variability present in the genotypes analyzed (1.0%0 range), as compared to those of previous studies: 4.4%0 (Lambrides et al, 2004 ), 3.4%0 (Adiredjo et al, 2014a ), 2.5%0 (Virgona et al, 1990 ; Virgona and Farquhar, 1996 ). Unlike other studies in which the analyzed genotypes were selected for showing a wide range of CID, the low variability for this trait in our study may have allowed the detection of significant associations between TE and other traits.…”
Section: Discussionmentioning
confidence: 77%
“…The physiological traits considered by Sinclair ( 2012 ) are consistent with those most frequently investigated in relation to intrinsic TE, which are those related to the fluxes of water and carbon between the leaf and the atmosphere. Carbon isotope discrimination (CID), a reliable estimator of intrinsic TE used frequently for phenotyping (Tardieu, 2011 ; Masuka et al, 2012 ), has frequently been shown to be only poorly correlated to whole-plant TE in different species (e.g., Krishnamurthy et al, 2007 ; Devi et al, 2011 ; Adiredjo et al, 2014a ). If the response of water fluxes to environmental variables are, however, studied at whole-plant level, a better correlation to whole-plant TE is usually found (e.g., Devi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result was also demonstrated by Ainsworth and Mc-Grath (2010). Comparing P n and T r in the two species, a lower WUE ge in Q. variabilis was obtained due to its different physiological and morphological traits, such as larger leaf area, rapid growth, and higher stomatal conductance than that in P. orientalis (Adiredjo et al, 2014). Medlyn et al (2001) reported that stomatal conductance of broadleaved species is more sensitive to elevated [CO 2 ] than conifer species.…”
Section: Differences Between Wue Ge and Wue Cpmentioning
confidence: 99%
“…Carbon isotope signature of plant tissues can reflect long-term plant responses to different environmental conditions and stresses (Vogel et al 1993) through the assessment of water use efficiency in plants (Tognetti et al 2000;Adiredjo et al 2014). …”
Section: Carbon Isotope Signature (δ 13 C)mentioning
confidence: 99%